Thank you for the opportunity to help you with your question!

a) f of g=f(g(x)). Meaning in every x of f(x), we replace it with (x+8)

f of g= 6(x+8)^2+2(x+8)+6

f of g=6(x^2+16x+64)+2x+16+6

f of g=6x^2+96x+384+2x+22 = 6x^2+98x+406

b) g of x means that, {(6x^2+2x+6)+8}

=6x^2+2x+6+8

=6x^2+2x+14

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up